1980
DOI: 10.1029/ja085ia05p02043
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of plasma, energetic particles, and fields near synchronous orbit in the nighttime sector during magnetospheric substorms

Abstract: We discuss two phases of the substorm-associated magnetospheric dynamics in terms of the particles and fields at synchronous orbit. The first phase corresponds to the 'decreases' of energetic particle flux first identified by Erickson and Winckler (1973) and discussed by Walker et al. (1976) and Erickson et al. (1979). This phase begins one-half hour to one hour before the substorm onset and is characterized by (1) a distortion of the magnetosphere to a more taillike configuration caused by (2) an intensifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
107
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 178 publications
(109 citation statements)
references
References 37 publications
2
107
0
Order By: Relevance
“…particle injection) in energetic particle fluxes near local midnight at geosynchronous orbit is a typical feature of magnetospheric substorms (e.g. Sauvaud and Winckler, 1980). During substorms, a change in the magnetic field configuration is also observed which consists of a gradual stretching and rapid dipolarization at geosynchronous orbit (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…particle injection) in energetic particle fluxes near local midnight at geosynchronous orbit is a typical feature of magnetospheric substorms (e.g. Sauvaud and Winckler, 1980). During substorms, a change in the magnetic field configuration is also observed which consists of a gradual stretching and rapid dipolarization at geosynchronous orbit (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic field observations in the equatorial region of the inner magnetosphere and farther in the magnetotail lobe have shown that a reconfiguration of the magnetic field topology ("dipolarization") linked to a partial disruption of the near-Earth cross-tail current is associated with substorm onsets detected as breakups of auroral forms in the ionosphere [e.g., Sauvaud and Winckler, 1980;Lui, 1988Lui, , 1996 All the processes discussed so far are generally presented as single entities; i.e., an isolated substorm would be associated with a single injection, a plasma sheet thinning, and a plasmoid formation. There are, however, numerous experimental pieces of evidence showing that even single substorms are made of recurrent and impulsive processes.…”
Section: Introductionmentioning
confidence: 99%
“…During periods of southward directed interplanetary magnetic field, when the solar wind energy can be directly coupled to the magnetosphere, the role of the cross tail current sheet has been recognized as fundamental in energy storage, plasma energetization andmagnetic fieldreconftguration (e.g., McPherron, 1972;Russell and McPherron, 1973;Lui, 1978;Sauvaud and Winckler, 1980;Nishida, 1983;Fairfield, 1984;Kaufmann, 1987;Lui et al, 1992).…”
Section: Introductionmentioning
confidence: 99%